Some generating functions of modified Bessel polynomials from the view point of Lie group - Asit Kumar Chongdar (International Journal of Mathematics and Mathematical Sciences)
In this paper we have derived a class of bilateral generating relation for modified Bessel polynomials from the view point of Lie group. An application of our theorem is also pointed out.